1998
DOI: 10.1021/ic970694l
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure, Electronic Structure, and Temperature-Dependent Raman Spectra of Tl[Ag(CN)2]:  Evidence for Ligand-Unsupported Argentophilic Interactions

Abstract: The structure of thallium dicyanoargentate(I) has been determined crystallographically. The crystal structure shows an Ag-Ag distance of 3.11 Å. This is the shortest Ag-Ag distance reported for any silver dicyanide salt whose crystal structure has been determined. Raman spectra of the compound show four nu(C)(-)(N) peaks that are well-resolved in the 10-80 K temperature range. This result agrees well with group theory analysis. Extended Hückel calculations using relativistic wave functions have been carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
137
0
5

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(151 citation statements)
references
References 105 publications
9
137
0
5
Order By: Relevance
“…), but significantly lower than those found in Tl[Ag(CN) 2 ] (2107, 2250 cm À1 ) [10] and other silver cyano complexes. [13] Generally, n Ä(CN) of a terminal MÀCN group shifts to a higher frequency if it forms a bridge of the MÀCNÀM' type derived from s coordination of the weakly antibonding nitrogen lone pair to a second metal center M'.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…), but significantly lower than those found in Tl[Ag(CN) 2 ] (2107, 2250 cm À1 ) [10] and other silver cyano complexes. [13] Generally, n Ä(CN) of a terminal MÀCN group shifts to a higher frequency if it forms a bridge of the MÀCNÀM' type derived from s coordination of the weakly antibonding nitrogen lone pair to a second metal center M'.…”
mentioning
confidence: 56%
“…We then used a zirconium catalyst in asymmetric Strecker reactions. In the presence of a zirconium catalyst (10 mol %) that was prepared from Zr(OtBu) 4 , (R)-6,6'-dibromo-1,1'-bi-2-naphthol ((R)-6-Br-BINOL, 2 equiv), [9] and N-methylimidazole (NMI, 3 equiv), aldimine 1 a was treated with Bu 3 SnCN [10] in dichloromethane at À 45 8C. The reaction proceeded smoothly to afford the corresponding aaminonitrile in 70 % yield with 55 % ee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silver is by far the less investigated coinage metal in coordination chemistry, which can possibly be attributed to the poor solubility of silver(I) compounds in common solvents and the sensitivity toward photodecomposition [1]. On the other hand, it has been found that many factors such as the nature of the ligands, solvents, counter-anions, etc., appear to modulate the stereochemistry of silver complexes [2].…”
Section: Discussionmentioning
confidence: 99%